Bibliometric Analysis of Gold Open Access in India. Issue 1 (2nd January 2018) - Nazim, Mohammad
ABSTRACT: This study analyzes the current state of gold Open Access (OA) in India based on papers published in the Web of Science indexed journals. It specifically focuses on research output published in OA journals and examines the difference between gold OA and general research output for papers authored by Indian researchers. In order to analyze the Indian contribution of gold OA literature and compares with other countries, Web of Science™-Core Collection was used. There is an increasing trend of contributing research papers in OA journals by Indian researchers. Among the top 20 publishing countries India ranks 10th place in terms of the general research output, but secures 8th place in terms of gold OA papers. However, India's position in terms of share of gold OA publications is relatively higher than other leading countries of the world. Researchers in India mostly prefer to contribute their gold OA papers in Indian journals rather foreign journals and the proportion of gold OA research output in Clinical, Preclinical, Health, Life Sciences and Physicals Sciences is much higher than other disciplines such as Arts & Humanities and Social Sciences. Since most of the research output in India is published in local journals, the study suggests further analyses of publications which are not published in Web of Science indexed journals.